Clinical application of parathyroid autotransplantation in endoscopic radical resection of thyroid carcinoma - Zhang, Qi; Qu, Kun-Peng; Wang, Ze-Sheng; Gao, Jing-Wei; Zhang, Yu-Peng; Cao, Wei-Jia (Frontiers in Oncology, 2022)
Purpose This study aimed to examine the effect of selective inferior parathyroid gland autotransplantation on central lymph node dissection(CLND) and incidence of postoperative hypoparathyroidism in patients undergoing endoscopic radical resection of thyroid carcinoma. Methods The data of 310 patients undergoing endoscopic radical resection of thyroid carcinoma will be retrospectively analyzed. The patients will be divided into the experimental group and the control group according to whether they combined with parathyroid autotransplantation. Statistics of the incidence rate of postoperative hypoparathyroidism, the concentration of PTH and Calcium in the systemic circulation at different time points in the two groups, the concentration of PTH in the cubital fossa vein in the transplantation region in the experimental group, and the number of central lymph nodes and positive lymph nodes dissection will be carried out. Results The incidence rate of temporary and permanent hypoparathyroidism in the experimental group was 33.75% and 0.625%, respectively, and in the control group was 22% and 5%, respectively; its difference was statistically significant (X2 = 10.255, P=0.006). Parathyroid autotransplantation increased incidence of transient hypoparathyroidism (OR, 1.806; Cl, 1.088-2.998; P=0.022), and lower incidence of permanent hypoparathyroidism (OR, 0.112; Cl, 0.014-0.904; P=0.040). The diameters of thyroid cancer nodules was not associated with the occurrence of transient hypoparathyroidism (OR, 0.769; Cl, 0.467-1.265; P=0.301) or permanent hypoparathyroidism (OR, 1.434; Cl, 0.316-6.515; P=0.641). Comparison of systemic circulation PTH, between the two groups showed that the PTH of patients in the experimental group was higher than that in the control group from 1 week to 12 months after the operation, and the difference was statistically significant (P<0.05). In the experimental group, from 1 week to 12 months after surgery, PTH concentrations was significantly higher in the cubital fossa of the transplantation side than in the contralateral side, and the differences were statistically significant (P<0.05). The mean number of central lymph node dissected per patient was significantly higher in the experimental group (7.94 ± 3.03 vs. 6.99 ± 2.86; P <0.05); The mean number of positive nodes per patient was significantly higher in the experimental group (3.16 ± 1.86 vs. 2.53 ± 1.59; P <0.05). Conclusions In endoscopic radical resection of thyroid carcinoma, parathyroid autotransplantation is more beneficial to postoperative parathyroid glands function recovery, effectively preventing postoperative permanent hypoparathyroidism and realizing more thorough CLND.